2012
DOI: 10.1111/j.1442-200x.2012.03633.x
|View full text |Cite
|
Sign up to set email alerts
|

Job discrimination against childhood cancer survivors in Japan: A cross‐sectional survey

Abstract: In Japan, employment-related discrimination still occurs in a small number of companies and public offices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Other descriptive studies noted a lower level of education status, employment status, and marital status . Previous studies in Japan have also suggested that childhood cancer survivors experience employment difficulties, low marriage rate, and psychological distress . The present results indicate that encountering difficulties in daily life as a result of a disease and its treatment may contribute to these unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…Other descriptive studies noted a lower level of education status, employment status, and marital status . Previous studies in Japan have also suggested that childhood cancer survivors experience employment difficulties, low marriage rate, and psychological distress . The present results indicate that encountering difficulties in daily life as a result of a disease and its treatment may contribute to these unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…Items 5 and 14 were removed and the correlation between item 3 and item 4 was added, and the model fit markedly improved. The final model, which included 23 items and six factors revealed an acceptable new model fit, χ 2 /df = 2.2, GFI = 0.91, CFI = 0.94, RMSEA = 0. 056, SRMR = 0.065.…”
Section: Resultsmentioning
confidence: 92%
“…One concern is that cancer patients may suffer discrimination and rejection in social interactions. [2][3][4][5] Such negative reactions in the general public towards a person or group based on stereotypical attributes that differentiate them from others in society is defined as public stigma. 6 Public stigma has a very negative influence on the health care of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the evidence employed quantitative methods ( n = 20) and was predominately published before 2010 ( n = 30; see Table 1). Stigma and workplace discrimination were examined across a wide range of cancer diagnoses, including breast cancer (e.g., Stewart et al, 2001), Hodgkin’s disease (e.g., Wasserman, Thompson, Wilimas, & Fairclough, 1987), leukemia (e.g., Zevon, Neubauer, & Green, 1990), colorectal cancer (e.g., Paraponaris, Teyssier, & Ventelou, 2010), and childhood cancers (Asami, Ishida, & Sakamoto, 2012; Evans & Radford, 1995; Green, Zevon, & Hall, 1991; Hays et al, 1992; Olson, Hung, Bobinski, & Goddard, 2011; Wasserman et al, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…In a study completed in Singapore, 81% of the public surveyed indicated that they would not hire a cancer survivor if they were in a position to make hiring decisions (Chen et al, 2006). A common employment practice that enhanced the likelihood of hiring discrimination was the request for medical documentation or a health certificate (Asami et al, 2012). For example, Mak et al (2014) also revealed how some survivors have been asked, “Have you ever suffered any serious, major illness?” or “Are you on long-term medication?” (p. 273), when applying for a job.…”
Section: Resultsmentioning
confidence: 99%